Ursolic acid : a novel antiviral compound inhibiting rotavirus infection in vitro - Tohmé, M. J. (2019)
Rotavirus is one of the leading causes of severe acute gastroenteritis in children under 5 years of age, mainly affecting developing countries. Once the disease is acquired, no specific treatment is available; as such, the development of new drugs for effective antirotaviral treatment is critical. Ursolic acid is a pentacyclic triterpenoid with antiviral activity, which has been studied extensively in vitro and in vivo. To study the potential antirotaviral activity of ursolic acid, its toxic potential for viral particles (virucidal effect) and cultured cells (cytotoxicity) was analysed. No effect on virion infectivity was observed with treatments of up to 40 µM ursolic acid, while incipient cytotoxicity started to be evident with 20 µM ursolic acid. The antiviral potential of ursolic acid was evaluated in in-vitro rotavirus infections, demonstrating that 10 µM ursolic acid inhibits rotavirus replication (observed by a decrease in viral titre and the level of the main viral proteins) and affects viral particle maturation (a process associated with the endoplasmic reticulum) 15 h post infection. Interestingly, ursolic acid was also found to hamper the early stages of the viral replication cycle, as a significant reduction in the number and size of viroplasms, consistent with a decrease in VP6 and NSP2 viral proteins, was observed 4 h post infection. As such, these observations demonstrate that ursolic acid exhibits antiviral activity, suggesting that this chemical could be used as a new treatment for rotavirus.